BENTUK PERTUNJUKAN TORTOR SOMBAH PANISUMBAH PADA MASYARAKAT SIMALUNGUN - lusiana rusadi (Universitas Negeri Medan, 2014)
The aim of this study is to determine how the origins and the performance forms in Tortor Somboh Panisumbah in Simalungun society. The teoritical backgrounds used in this study are the theories related to topic of discussion, the method used in this experiment is a qualitatie descriptive method, the data are collected though both field observation and interviewing with some people. The sample in this study is artist, dancer, and people who understand about Tortor Sombah Panisumbah. The result of this study shows that Tortor Sombah Panisumbah is a usual ritual treatment performed by simalungun society. It’s usually done in Parsimangotan. This dance is performed by man in a certain move that has continuity between movement and music tempo, the costume worn by dancer is the traditional costume in Simalungun which is long black shirt, hiou clothes, gotong hat. The accompanying music is haro-haro, gual parahot, rambing-rambing, gual batara guruh simbolon . The traditional music instruments in Tortor Sombah Panisumbah are gondrang, ogung ,sarunei. There is no specific pattern on this dance , it’s based on the performance need. Keyword: Tortor Sombah Panisumbah